Image Guided Frontal Sinus Mapping: Our Technique - Premjit S Randhawa; Gentle Wong; William E Grant (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2015)
Access to the frontal sinus is challenging and both external and endoscopic approaches are described in the literature. Where an external approach is indicated, a bicoronal osteoplastic flap procedure is generally preferred as this reduces fronto-ethmoidal recess stenosis and allows obliteration if required [1]. Precise demarcation of the anatomy of the frontal sinus is crucial when using this technique to avoid inadvertently entering the anterior cranial fossa.